(untitled) (Research, Society and Development, 2023)
Yeast Candida spp. can cause serious infections, especially in patients of the hospital environment. Variation in the virulence profile of Candida clinical isolates and high mortality rates indicate the importance of rapid and accurate identification, as well as susceptibility testing for successful candidiasis treatment. A total of 20 strains were isolated from patients from Tertiary Hospital of the Northern Zone of Ceará. PCR amplification followed by agarose gel electrophoresis (PCR-AGE) and the manual method (culturing on CHROMagar-Candida) and VITEK automated method were used to test a total of 20 fungal strains from clinics sources. Five strains of C. albicans, 2 of C. tropicalis and 4 strains of C. parapsilosis which were cultured for the determination of MIC (Minimum Inhibitory Concentration). The best sensitivity rate was demonstrated by automatic identification and PCR-AGE, where all 20 strains isolated with a sensitivity profile of 100% (20/20) were completely identified. According to the data obtained, resistance to amphotericin B (CIM ≥ 1 µg/ml) was observed in some isolates of C. tropicalis and C. parapsilosis. However, for the other antifungals, these same species presented 100% sensitivity (MIC ≤ 0.125 μg / ml; MIC ≤ 8 μg / ml). Isolates of C. albicans were sensitive to all antifungal agents with 100% sensitivity, although 75% of the isolates showed a tendency for less susceptibility to amphotericin B. In this study, we confirmed the efficacy and applicability of PCR-AGE in the identification and differentiation of yeast Candida spp. from clinical samples.